2004
DOI: 10.1074/jbc.m400613200
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Carbon Monoxide Binding to CooA

Abstract: CooA is a dimeric CO-sensing heme protein from Rhodospirillum rubrum. The heme iron in reduced CooA is six-coordinate; the axial ligands are His-77 and Pro-2. CO displaces Pro-2 and induces a conformation change that allows CooA to bind DNA and activate transcription of coo genes. Equilibrium CO binding is cooperative, with a Hill coefficient of n ‫؍‬ 1.4, P 50 ‫؍‬ 2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
82
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(89 citation statements)
references
References 27 publications
7
82
0
Order By: Relevance
“…These substitutions do not lie near the DNA-contacting surfaces and are best explained by their creating a shift in the equilibrium such that a larger fraction of the CooA population is truly active. Another line of evidence discussed below, is from kinetic analysis, which has shown that there are two different states of the heme in a population of CO-bound wild-type CooA, as revealed by substantially different CO off-rates (103). Lastly, the failure to obtain crystals of the CO-bound CooA is consistent with the hypothesis of the heterogeneity of this form.…”
Section: Population Dynamics Of the Cooa Response To Comentioning
confidence: 49%
“…These substitutions do not lie near the DNA-contacting surfaces and are best explained by their creating a shift in the equilibrium such that a larger fraction of the CooA population is truly active. Another line of evidence discussed below, is from kinetic analysis, which has shown that there are two different states of the heme in a population of CO-bound wild-type CooA, as revealed by substantially different CO off-rates (103). Lastly, the failure to obtain crystals of the CO-bound CooA is consistent with the hypothesis of the heterogeneity of this form.…”
Section: Population Dynamics Of the Cooa Response To Comentioning
confidence: 49%
“…Further discussion of this model for NO dissociation from sGC can be found in a previous report (29). Additionally, analogous models have been proposed to explain multiple exponentials observed for ligand binding to hexacoordinate globins (40) and to the CO sensor CooA (41).…”
Section: Resultsmentioning
confidence: 99%
“…CooA regulates the pathway, binding CO to activate expression of genes for oxidation of CO to CO 2 and reduction of protons to H 2 (57). CooA is a homodimeric heme-binding cAMP receptor protein (CRP) transcriptional regulator family member that binds CO cooperatively (58). Inactive ferric CooA has a Cys-75 thiolate heme ligand, which switches to His-77 in ferrous CooA.…”
Section: Cooamentioning
confidence: 99%